Doppler-Guided Versus Digitally Guided Transanal Hemorrhoidal Dearterialization: A Systematic Review and Meta-Analysis - Massoni, Marília Cardoso; Marimpietri, Felipe Santos; Silva, Paulo André Lago; de Abreu, Glicia Estevam (Journal of Coloproctology, 2025)
Transanal hemorrhoidal dearterialization (THD) has emerged as a minimally invasive alternative to conventional hemorrhoidectomy, often performed with Doppler guidance (DGHAL) to facilitate arterial ligation. However, some studies suggest that digitally guided THD (HAL) may offer comparable outcomes with reduced costs. This systematic review and meta-analysis aim to compare the efficacy and safety of DGHAL versus HAL in patients with hemorrhoidal disease.Following PRISMA 2020 guidelines, a systematic review was registered in PROSPERO (CRD42024625878). Searches in PubMed, EMBASE, and Cochrane Library identified randomized controlled trials (RCTs) comparing DGHAL and HAL. Primary outcomes included prolapse recurrence, postoperative bleeding, pain, and operative time. Statistical analyses were performed using RevMan 5.4, with odds ratios (OR) and mean differences (MD) at 95% confidence intervals (CI). Risk of bias was assessed using Cochrane RoB 2.Ten RCTs with 961 patients were included. No significant differences were found between DGHAL and HAL in late bleeding (OR 1.38, 95% CI 0.68–2.79, P = 0.62), prolapse recurrence at one year (OR 1.60, 95% CI 0.62–4.13, P > 0.05), intermediate pain (MD 0.78, 95% CI -0.51–2.07, P = 0.24), or operative time (MD 3.87 min, 95% CI -18.94–26.67, P > 0.05).Digitally guided THD appears to be a cost-effective alternative to Doppler-guided THD, with comparable outcomes in terms of bleeding, prolapse recurrence, postoperative pain, and operative time. These findings suggest that the additional cost of Doppler guidance may not be justified in routine clinical practice. Further studies focusing on specific patient subgroups may help refine indications for each technique.
Keywords: hemorrhoidal disease; transanal hemorrhoidal dearterialization; doppler-guided hemorrhoidal artery ligation; hemorrhoid surgery; meta-analysis